Respiratory Epithelial Adenomatoid Hamartoma of the Nose: An Updated Review. Issue 5 (September 2014) - Nguyen, Duc Trung; Gauchotte, Guillaume; Arous, Fabien; Vignaud, Jean-Michel; Jankowski, Roger
Background: This study was designed to update clinical and imaging features as well as treatment outcomes of the nasal respiratory epithelial adenomatoid hamartoma (REAH). Data sources included case reports, original articles, and reviews published in English or French in PubMed from 1995 to date. Methods: Only published articles that met Wenig's histological criteria for the diagnosis of REAH were included. Results: REAH is not rare and is probably underdiagnosed. It is usually observed in the fifth decade of life with a 3:2 male/female predilection. REAH can be represented in two forms: as an isolated lesion (less frequent) or in association with an inflammatory process (especially nasal polyposis). It was observed in 35–48% of patients undergoing endoscopic endonasal surgery for nasal polyposis. Its origin is found, in most cases, in the olfactory cleft, which is exhibited on computed tomography (CT) scans by widened opacified olfactory clefts without bone erosion. Resection of REAH from the olfactory clefts does not worsen, but instead, can improve the sense of smell after surgery. Conclusion: Looking for REAH on CT scans and during endoscopic examination can lead to its diagnosis and help avoid aggressive surgical procedures and their complications. Endoscopic resection is the treatment of choice. The removal of REAH constitutes a specific surgery on the olfactory clefts, which can improve nasal obstruction as well as sense of smell. Whether REAH can be defined as a hamartoma, an inflammatory reactive process, or a neoplastic lesion remains to be determined.